2017
DOI: 10.3390/min7070128
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Reuse of Mine Tailings and Waste Rock as Water-Balance Covers

Abstract: Abstract:The focus of this study was to evaluate the potential reuse of mixed mine tailings and waste rock in water-balance covers (WBCs). Reuse of mine waste in geoengineering applications can provide an economic advantage via offsetting raw material requirements and reducing waste volumes to manage. Water-balance covers are designed to minimize percolation and/or oxygen ingress into underlying waste via moisture retention while also providing resistance against slope failure and erosion of cover materials. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…However, the silicate adsorbents that have been reported were powdered and granulated; these forms of adsorbents were difficult to separate from the solution, and secondary pollution arose easily [23][24][25]. To find a simple and inexpensive method for separating adsorbents from solution, preparing the adsorbent into a stable structure such as a block with pores is a convenient way to realize this goal [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the silicate adsorbents that have been reported were powdered and granulated; these forms of adsorbents were difficult to separate from the solution, and secondary pollution arose easily [23][24][25]. To find a simple and inexpensive method for separating adsorbents from solution, preparing the adsorbent into a stable structure such as a block with pores is a convenient way to realize this goal [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The innovative methods currently used in managing Pt mine waste include crusher plants that turn underground mine waste rock into various construction products. The crusher plants perform opencast mining activities which are part of the growing small-scale mining sector [7]. However, these facilities' mining processes involve crushing and screening of the mine waste rock, which inevitably produces dust particles.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational health and safety (OHS) should remain the number one priority in mining. A research study showed that mining operations were still the leading cause of exposures harmful to health and associated with various causes of occupational accidents and diseases [7]. For example, in SA, Pt mining contributed 25 fatalities and injuries between January and October 2017, with similar statistics for 2016 within the same period [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the most important issues facing the mining industry is the sensible management of existing and previously unused resources of mining waste stored in MWTF. Research on the use of waste raw materials from the extraction and processing of rock raw materials is carried out in Poland and around the world [1][2][3][4][5]. However, the review showed that there is still a problem associated with the possibilities of using waste generated in the mining sector of rock raw materials.…”
Section: Introductionmentioning
confidence: 99%